Uji Kandungan Plumbum (Pb) Dalam Urine Karyawan SPBU Bayaoge Kota Palu - Astini Dewi Sari; Musjaya M. Guli; Miswan Miswan (Biology Department, Mathematics and natural science, Tadulako University, 2013)
A study about the test of plumbum (Pb) contents in urine Bayaogegas station employer of palu has doneat from November to December 2012. The aim of this study todetermine thecontent of plumbum(Pb) in urine Bayaogegas station Palu. Samples that were analyzed in this study were 9 urine samples with different tenure. The result showed that there were 2 urine samples of Bayaoge gas station employer has exceeded the threshold while 7 urine samples still below the threshold are allowed in the body. Key words: Plumbum, urine, SPBU (service station) Bayoge Palu